THE POTENTIAL OF USING THE ARTIFICIAL INTELLIGENCE TECHNOLOGY IN THE ACTIVITIES OF CREDIT INSTITUTIONS - Popelo , O. V.; Dubyna , M. V. (The actual problems of regional economy development, 2024)
In the article, theoretical and applied provisions of using the artificial intelligence technology in the activities of credit institutions are considered. This was done by analyzing the essence of this technology and the specifics of its use in the functioning of business entities. The history of the origin of this technology is considered in fragments, and its individual components are identified, without which it cannot exist, including the following: machine learning systems, deep learning, neural networks. This made it possible to further analyze certain types of the artificial intelligence technology and identify the following ones: reactive artificial intelligence technologies, limited memory technologies, theory of mind technologies, self-aware technologies. The article focuses on the analysis of modern approaches of scientists and specialists in the field of the development of the artificial intelligence technology regarding the threats and benefits of its use in the economic system, and its impact on the current development of society. This made it possible to establish that the one of the most active areas, in which the potential of artificial intelligence is being actively used for the development today, is the financial services sector. In the article, a thorough analysis of the application of the artificial intelligence technology is the functioning of credit institutions. In particular, the main areas of use of this technology in the work of these institutions were identified, namely: analysis of the borrowers' creditworthiness, automation of decision-making, security monitoring and fraud prevention, customer information support and automation of credit services, marketing activities to create personalized credit products, and search for areas for their sale to different groups of customers. In the article, current trends in the use of chatbots by credit institutions are also analyzed, as this is the area in which these institutions most often use certain elements of the artificial intelligence technology. Accordingly, the advantages and disadvantages of using chatbots in the work of these institutions are specified. In addition, in the article, various modern cases of using the artificial intelligence technology by domestic and global credit institutions are examined. This made it possible to identify the main problems that hinder the use of the artificial intelligence technology in Ukraine by credit institutions.